Cortical responses to sport-specific stimuli in a standing stop signal task. (November 2022) - Scharfen, Hans-Erik; Lehmann, Tim; Büchel, Daniel; Baumeister, Jochen
Abstract: Executive functions (EF) and especially inhibition have been shown to play an essential role in team sports. However, the underlying cortical mechanisms of EF in real game situations are barely understood, since previous studies predominantly used tests with simplified stimuli in seated positions. Consequently, the aim of the current study was to explore cortical responses to sport-specific stimuli in a standing stop signal task (SST). Cortical activity was investigated in 17 adult amateur soccer players using mobile electroencephalography (EEG) in a standard- (Std) and a sport-specific (Sp) SST. Whereas mean reaction times were significantly longer in the Sp-SST, stop error-rates demonstrated no significant difference. Further, analysis of event-related spectral perturbation (ERSP) in a frontal cluster also showed no significant differences between Std- and Sp-SST for go and stop conditions. Thus, sport-specific stimuli in a standing SST may exhibit similar inhibitory cortical processes as the standard SST, although requiring longer processing times with regards to the more complex visual stimulation. Future studies are needed to further develop realistic paradigms for evaluating sport-specific cognitive performance. Highlights: Sport-specific stimuli exhibited similar inhibitory cortical processes and stop-error rates as the standard stimuli. Sport-specific stimuli required longer reaction times with regards to the more complex visual stimulation. Present findings may serve as a first step towards a more realistic examination of sport-specific cognitive performance.